Development Of Critical Thinking And Creativity Skills In Educational Classes In Schools "In The Formation Of 4-K Skills" - Azizova Dilnoz Yoldashevna (Genius Publishing Group, 2024)
Critical thinking is one of the types of human intellectual activity, which is characterized by a high level of perception, understanding, objectivity of approach to the surrounding information field. In order to form creative skills in education classes, it is necessary to encourage the pupil's independent choice of goals and tasks in every way, to build students' confidence in their abilities.
Keywords: Critical Thinking; 2. Creativity (creative approach); Cooperation